Uncle Tom's Cabins : The Transnational History of America's Most Mutable Book - Mihaylova, Stefka; Davis, Tracy C., 1960- (Book collections on Project MUSE., 2018)
"As Harriet Beecher Stowe's novel Uncle Tom's Cabin traveled around the world, it was molded by the imaginations and needs of international audiences. For over 150 years it has been coopted for a dazzling array of causes far from what its author envisioned. This book tells thirteen variants of Uncle Tom's journey, explicating the novel's significance for Canadian abolitionists and the Liberian political elite that constituted the runaway characters' landing points; nineteenth-century French theatergoers; liberal Cuban, Romanian, and Spanish intellectuals and social reformers; Dutch colonizers and Filipino nationalists in Southeast Asia; Eastern European Cold War communists; Muslim readers and spectators in the Middle East; Brazilian television audiences; and twentieth-century German holidaymakers. Throughout these encounters, Stowe's story of American slavery serves as a paradigm for understanding oppression, selectively and strategically refracting the African American slave onto other iconic victims and freedom fighters. The book brings together performance historians, literary critics, and media theorists to demonstrate how the myriad cultural and political effects of Stowe's enduring story has transformed it into a global metanarrative with national, regional, and local specificity"--